MARJINALISASI PEDESAAN AKIBAT RELASI KUASA LOKAL DAN SUPRALOKAL - Yunindya Wati (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
This paper analyses the development of village as a sosial transformation in which it is always seen as a dynamic community and still exist on the continuum changes from time to time. To understand a sosial process in rural areas, especially related to the State as an super-local institution,it is necessary to consider the Law No. 5 of 1979 on the village governance. This is important because through that law,we can understand how the Stateintervene and shapes a lokal authority. This can be clearly seen through the uniformity of the village governance as an effort to gain a control mechanism over the local people. As a consequence, the State, in the name of development, create its agent within a rural governance.